ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI KESEHATAN MENTAL EMOSIONAL MASYARAKAT DI DUKUH GUMUK SARI DAN GERJEN, PUCANGAN, KARTASURA - Tunjung Sri Yulianti; Dinar Ariasti (KOSALA : Jurnal Ilmu Kesehatan, 2020)
Background. Mental health or mental emotional health is a condition of someone who continues to grow and maintain harmony in self-control, and free from serious stress. Advances in technology bring changes in people’s lifestyle and change in way of thinking that have consequences in mental health because not everyone can adjust, the result will be to couse tension and a tendency to increase mental health disorders. In Indonesia the number of cases of mental disorderes continues to grow which has an impact on increasing the country’s burden and decreasing human productivity. The Aim of the Study. To determine the factors that influence the mental emotional health of the community. Subject and Method. The subjects were residents of Dukuh Gumuk Sari and Gerjen, Pucangan, Kartasura. This is analytic research with correlation design, statistical test with logistic regression. Results. There is an influence of somatic factors (p value= 0.000 and OR=50,708), socio-cultural factors (p value= 0.004 and OR= 7,054) and psychological factors (p value= 0.058 and OR=3,800) on mental emotional health of the community. Conclusion. Somatic, socio-cultural and psychologic factors together have an influence on the emotional mental health of the community. Somatic factors have the greatest influence on the emotional mental health of respondents. Keywords: emotional mental health, psychological, social culture, somatic Korespondensi: Tunjung S. Yulianti. STIKES PANTI KOSALA SURAKARTA, Jalan Raya Solo - Baki KM. 4 Gedangan, Grogol, Sukoharjo, Jawa Tengah. Email: tejeyulianti@gmail.com.